2014
DOI: 10.3109/01443615.2014.960831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of home-based Kegel exercises on quality of life in women with stress and mixed urinary incontinence

Abstract: The aim of this study was to assess the effects of home-based Kegel exercises in women with stress and mixed urinary incontinence. A total of 90 women with urodynamically proven urinary stress (SUI) and mixed (MUI) incontinence awaiting anti-incontinence surgery were recruited in the urogynaecology clinic of Ankara Zekai Tahir Burak Women's Health Research and Education Hospital. Of these, 18 women were excluded due to low compliance and the remaining 72 were divided into two groups according to urodynamic dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 17 publications
3
31
0
3
Order By: Relevance
“…Thus, the majority of therapeutical approaches aim at strengthening the support of the pelvic floor, either conservatively or surgically. Although, there are reports on the beneficial effects of conservative treatment , patients have to be very compliant and the final outcome remains questionable. On the other hand, none of the existing surgical approaches is optimal as they are often associated with complications .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the majority of therapeutical approaches aim at strengthening the support of the pelvic floor, either conservatively or surgically. Although, there are reports on the beneficial effects of conservative treatment , patients have to be very compliant and the final outcome remains questionable. On the other hand, none of the existing surgical approaches is optimal as they are often associated with complications .…”
Section: Discussionmentioning
confidence: 99%
“…There are many approaches for treating UI; the conservative therapy includes lifestyle changes, pelvic floor muscle training (PFMT), bladder training, and electro‐magnetic stimulation of the pelvic floor muscles and drugs for UUI from OAB . A variety of surgical procedures are based on traditional Burch colposuspension and bladder‐neck slings and their modifications .…”
Section: Introductionmentioning
confidence: 99%
“…They opined that home-based Kegel exercises, with no supervision are effective in women with SUI and MUI and the improvement is better in women with SUI. 16 Above studies indicates discrepancies in results of various methods. There is also different opinion as far as pelvic floor muscle exercise is concerned.…”
mentioning
confidence: 99%
“…They concluded that even home based Kegel exercise if suitably trained is useful for the management of stress urinary incontinence and there is no need of supervision. 9 Bo K, Talseth T and Holme I in a single blind, randomized controlled trial of the pelvic floor exercises, electrical stimulation, vaginal cones and no treatment category for the management of genuine stress incontinence observed that pelvic floor muscle training was better than other methods. 10 Rodrigo A Castro also had the similar conclusion and recommended that pelvic floor muscle exercise should be offered as the first choice of treatment for the management of stress urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%